The Role of the Digital Economy in Increasing Employee Performance - Rizky Ferrari Oktavian; Uswatun Hasanah (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The objective of this research is to test the role of the digital economy on the performance of employees at HDS Furniture Bandung City. This research is done with use approach quantitative. The population of this research is the then Bandung City Furniture HDS employees chosen by purposive sampling, so amount sample is as many as 40 employees. Data collection was carried out through a deployment questionnaire to respondents. Obtained data were then processed and analyzed using multiple linear analyses with SPSS software. Findings This research proves that Digital Platform Capability has an effect positive to performance employee. This study is expected can give contribute especially in the realm of knowledge HR management and sharing company that with managing employees can give good impact to achieve objective company. The activity plan is divided into four stages starting with the first stage month of preparation June. up to the fourth stage in the form of a final report for December 2022. The result of this research shows that in a manner descriptive variable Digital Platform Capability is in a good category.the